The Reality of the Medical Waste Management in Dental Clinics Case Study: Dental Clinic in Khan Younis Governorate - Azzam, Esraa Mosbah; El-Ashgar, Nizam M. (Journal of Risk and Crisis Management, 2019)
This study aimed to evaluate the status of medical waste management in dental clinics in Khan Younis governorate (case study) in terms of sorting of hazardous medical waste, collection of waste in sealed bags when filled, transportation through transport trucks for the disposal of medical waste. The researchers used field interview methodology and the direct observation of the clinic and ask a set of questions to the staff in the clinic. The most important findings of the study that there was no proper process of sorting of medical waste where it is random and there was no application of instructions of the laws of the World Health Organization for waste management properly so that it is disposed of by the Ministry of Health in Gaza Governorates incinerators. The study recommended the need for a special system for sorting of hazardous medical waste from non-hazardous medical waste at the source of its production in proper methods and promoting the development of legislation as policies for the management of health waste for health safety and raising awareness among health institutions employees about the concept of medical waste management.
Keywords: Medical waste; Medical waste management; Gaza Strip; Hazardous materials; Hazardous biological waste